The Measuring Productive Efficiency for Analyzing the Sales Activity in Hospitality Sector: AL Mansour Melia Hotel" - Abdalamir Abd Kahdum, Karrar Abdulelah Azeez, Mohammed Saleh Mahdi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper aims to measure the productivity efficiency in the hospitality sector, which identify the food and drinks level for sales. The study analyzes the efficiency for employees, capacity, raw materials as inputs on tourism processing that may guide to share excellent services and sales. The data of (2017-2018) considered accessing the results that associated the productivity efficiency within sales activity. The sampling was depended sales, labour cost, power cost, raw materials cost, employees number, and departments number which calculated by multiple models for testing the hypothesis research. Findings showed that inputs higher than outputs; consequently, the productivity efficiency improved the performance of tourism firm for all factors. It also improves the department performance of the hotel, which have a high level of tourist satisfaction, namely the dining hall and reception hall. That an improvement of the hotels’ services efficiency is needed, through the implementation of quality management strategy, having as main objective to enhanced glassy of tourists’ satisfaction.